Study on the impact performance of RC fences strengthened with high strength strain-hardening cementitious composites - Wu, C. (Elsevier Ltd, 2022)
This paper presents a numerical study on the impact performance of reinforced concrete (RC) fences strengthened with high-strength strain-hardening cementitious composite (HS-SHCC) through finite element (FE) modeling. To accurately simulate the peculiar material characteristics of HS-SHCC, the MAT72R3 material model was calibrated and verified against experimental data. A comparison study for RC and HS-SHCC panels subjected to drop hammer impact was conducted to observe the impact performance of HS-SHCC. Results showed that the impact resistance and energy dissipation capacity of HS-SHCC are significantly higher due to its high strength and high ductility. A full-scale study of pick-up truck collisions was then conducted to investigate the response, failure, and best strengthening configuration of conventional RC fences strengthened with HS-SHCC layers. Results showed that both strengthened configurations under moderate impact energy could significantly improve the impact resistance and reduce the residual deflection. While in the case of large impact energy, the back-strengthened RC fence gave notably better performance and higher impact resistance due to the composite effects between RC and HS-SHCC layers. Based on the analysis of the failure modes and energy dissipation, the mechanism of such composite effects was summarized. Â© 2022